Monodisperse colloidal spheres with a high refractive index: their synthesis, assembly and application in structural colored materials. Issue 46 (16th November 2022) - Yu, Tongling; Bi, Jiajie; Wei, Wuke; Su, Xin
Abstract : The review summarizes recent advances in preparing monodisperse colloidal spheres with a high refractive index, effective methods for assembling these spheres into structural color materials and their intriguing optical properties with related applications. Abstract : Due to photonic bandgaps (PBGs) for tuning the luminescence of light emitters together with metallic and fadeless structural colors, photonic crystals (PCs) have been considered as appealing functional optical materials and have stimulated applications in various fields. The attractive optical properties of PCs are highly dependent on the refractive index contrast between the construction materials of PCs. Therefore, monodisperse colloidal spheres with a high refractive index have shown great potential as ideal building blocks for fabricating PCs with stronger bandgaps and brilliant structural colors. In recent decades, the design strategy and controllable preparation of monodisperse colloidal spheres with a high refractive index have witnessed tremendous progress. Herein, based on the nature of the structure, recent experimental advances in preparing various kinds of monodisperse colloidal spheres with a high refractive index and effective methods for assembling these spheres into PCs or amorphous structurally colored materials have been summarized. Specific attention is focused on the interesting and unique optical properties of these structurally colored materials and their related optical applications. In addition, potential challenges and improvements in the future in this field are presented.